Effects of ingredients and processing conditions on the quality frozen dough bread made from diferent wheat flour - Ruska, Laslo; Timar, Adrian (Acta Agraria Debreceniensis, 2010)
A laboratory scale no-time frozen dough procedure that approximates Romanian commercial practice has beendeveloped and used to study the effects of ingredients and processing conditions on the bread quality of a straightgrade wheat flour during prolonged storage (2 days to 26 weeks). All treatments (baking absorption level, mixingenergy input, mixer type, fermentation and intermediate proof times, removal of oxidant and/or doughstrengthening conditioners and partial freeze-thaw cycles) had significant effects (P 1 h) and removal of oxidant and/or surfactants hadthe most dramatic effects. Addition of a very strong flour at 30% to strengthen the wheat flour had no significanteffect (P>0.05) upon bread quality under optimum conditions.